Modulation of Interleukins in Sepsis-Associated Clotting Disorders: Interplay With Hemostatic Derangement. (January 2017) - Low, Christopher; Syed, Daneyal; Khan, Daniel; Tetik, Sermin; Walborn, Amanda; Hoppensteadt, Debra; Mosier, Michael; Fareed, Jawed
Interleukins play a central role in the immune system and are involved in a variety of immunological, inflammatory, and infectious disease states including sepsis syndrome. Levels of interleukins may correlate with overall survival and may directly or indirectly affect some of the regulators of coagulation and fibrinolysis, thereby disrupting hemostasis and thrombosis. Our hypothesis is that in sepsis-associated coagulopathies (SACs), interleukins may be upregulated, leading to hemostatic imbalance by generating thrombogenic mediators. We profiled the levels of interleukins IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-8, and IL-10 in addition tod -dimer (DD) in patients with SAC and in normal donors. We observed the highest increase in interleukins IL-6 (322-fold), IL-8 (48-fold), IL-10 (72-fold), and DD (18-fold). This suggests that interleukins such as IL-6 and IL-10 have a close association with coagulopathy and fibrinolytic dysregulation in sepsis and can be considered as candidates for potential therapeutic targets in SAC.